Committing Digital Music Piracy: A Study in Penang (Journal of Economics and Sustainability, 2022)
Piracy is one of the primary challenges facing the music industry. Music piracy has accounted for substantial revenue losses in this industry in Malaysia, a country in which intellectual property regimes are deemed as a matter of concern. If music piracy is left unchecked, it may destroy the value chain of the music industry. This study aims to explore the extent to which digital music copyright violations prevails in society and examine the characteristics of copyright violators. The analysis was carried out using primary data collected from a survey carried out in Penang, a highly urbanised state in Malaysia. A descriptive approach was used for the analysis. The findings from this study offer insights into the phenomenon of music piracy in Malaysia. The incidence of violating copyright was high, with seven out of ten persons involved in illegally using digital music. Copyright violators have distinguishing characteristics that differentiate them from non-copyright violators. The results found that awareness about intellectual property rights was rather low among violators and that they had misconceptions about music piracy. While most participants agreed that effective enforcement was critical in reducing illegal music activities, fewer perceived the risks of being caught and the high costs associated with punishment. Policies aimed at increasing awareness and understanding of intellectual property rights and the possible societal implications of copyright issues were discussed. The need to enhance copyrightenforcement protection in the country is also highlighted.